Influence of periodontal treatment on blood microbiotas: a clinical trial - Zhang,Wenyi; Meng,Yang; Jing,Jin; Wu,Yingtao; Li,Shu (PeerJ, 2021)
Objective To investigate the effects of periodontal treatment on the abundance and diversity of blood microbiota. Methods and Materials Twenty-seven periodontitis patients were randomly allocated to a control group (A) and two test groups (B1 and B2). Group A patients received full-mouth scaling and root planing (SRP), group B1 patients received subgingival glycine air polishing (GAP) right after SRP, and group B2 patients received subgingival glycine air polishing right before SRP. Peripheral blood samples were obtained at the baseline, the day after periodontal treatment, and 6 weeks after treatment and evaluated using nested polymerase chain reaction and 16SrRNA Gene Sequencing (Miseq platform). Results All participants exhibited significant improvements in the clinical parameters evaluated at the 6-week follow-up visit compared to the values at the baseline, but no significant differences were observed between the three groups. The total bacterial count was lowest in group B2. The bacterial species diversity (α-diversity) in group B1 was significantly higher (Chao-1 index, P = 0.03) and Porphyromonas and Pantoea were the dominant genera (linear discriminant analysis (LDA > 2)) in this group the day after treatment compared to the baseline. No significant difference was detected in the relative abundance and α-diversity of blood microbiota between the baseline and 6 weeks after treatment. Conclusion Local periodontal treatment merely disrupts the stability of blood microbiota in the short term. Periodontitis treatment using full-mouth SRP followed by adjunctive GAP is a promising approach to reduce the introduction of bacteria into the bloodstream during the procedure.
Keywords: Periodontitis; Blood microbiota; 16SrRNA; Glycine air polishing